Quantum magnetism in molecular spin ladders probed with muon-spin spectroscopy. (4th October 2018) - Lancaster, T; Xiao, F; Huddart, B M; Williams, R C; Pratt, F L; Blundell, S J; Clark, S J; Scheuermann, R; Goko, T; Ward, S; Manson, J L; Rüegg, Ch; et al.
Abstract: We present the results of muon-spin spectroscopy ( μ + SR) measurements on the molecular spin ladder system (Hpip)2 CuBr4(1− x ) Cl4 x, [Hpip = (C5 H12 N)]. Using transverse field μ + SR we are able to identify characteristic behaviour in each of the regions of the phase diagram of the x  = 0 strong-rung spin ladder system (Hpip)2 CuBr4 . Comparison of our results to those of the dimer-based molecular magnet Cu(pyz)(gly)(ClO4 ) shows several common features. We locate the crossovers in partially disordered (Hpip)2 CuBr4(1− x ) Cl4 x ( x  = 0.05), where a region of behaviour intermediate between quantum disordered and Luttinger liquid-like is identified. Our interpretation of the results incorporates an analysis of the probable muon stopping states in (Hpip)2 CuBr4 based on density functional calculations and suggests how the muon plus its local distortion can lead to a local probe unit with good sensitivity to the magnetic state. Using longitudinal field μ + SR we compare the dynamic response of the x  = 1 strong-rung material (Hpip)2 CuCl4 to that of the strong-leg material (C7 H10 N)2 CuBr4 (known as DIMPY) and demonstrate that our results are in agreement with predictions based on interacting fermionic quasiparticle excitations in these materials.